The usage of records management system in construction companies / Nurul Amalina Md Noor... [et al.] - Md Noor, Nurul Amalina; Ab Kahar, Nur Khatijah; Mustafa, Nur Fatin; Anor, Asmirrah (2014)
This chapter provides an overview of study which includes the context of the study that focuses on records management system in construction companies. This section is followed by the problem statements, research objectives and the background of the organization. It also highlights the methodology of orientation, scope of the study and significance of the study.